Reducing Anxiety Level in Mathematics Learning using Pedagogical Agent - Yeo, Wern Lin (2015)
The objectives of this study are to design pedagogical agents that will help students to reduce mathematics anxiety problem and to determine appropriate number and types of the anxiety treatment messages in a computer-based learning environment according to students’ anxiety levels. Participants in this study were 123 out of 180 undergraduates who were taking a Probability and Statistics course. The duration to conduct this study was around six months. There were few phases in this study. The first phase was designing the system and PAs for around four months. Second phase was students were given a consent form to obtain their permission to participate in this study. After the students agreed to participate in this study, they were given a duration of one week to fill up the pre-questionnaire online. The third phase was conducted for one month for the students to learn probability topics using the system, PMath Guide with pedagogical agents. These pedagogical agents in the system acted as a lecturer, tutor and motivator. In short, the pedagogical agents led students to have an interest in learning probability, providing encouragements, increasing confidence level, and thus reducing their anxiety level. The fourth phase was conducted for one week for the students to fill up an online post-questionnaire after they finished learning using the PMath Guide. The students’ anxiety level were determined by comparing the scores from mean and standard deviation from pre and post Mathematics Anxiety Rating Scale (MARS). Anxiety level was low when the scores were below one standard deviation from the mean scores. Meanwhile, anxiety level was categorised as average when scores were within one standard deviation from the mean scores whereas scores that were above one standard deviation from the mean scores was considered to have high anxiety level.